Combining service and learning in higher education : evaluation of the Learn and Serve America Higher Education program - Gray, Maryann Jacobi (RAND Education, 1999)
This report presents results of a three-year evaluation of Learn and Serve America, Higher Education (LSAHE), a program sponsored by the Corporation for National and Community Service that aims to increase involvement in community service by higher education institutions and students. LSAHE emphasizes an approach to community service, called "service-learning," that focuses on the development of service providers as well as service recipients. Between 1995 and 1997, about one in every eight higher education institutions nationwide participated in LSAHE by developing service-learning courses and programs. The evaluation described the major activities and accomplishments of LSAHE-supported programs; assessed the impacts of LSAHE on students, communities, and institutions; and determined returns on the public investment in LSAHE. Results show that LSAHE was highly successful in serving communities and had mixed success in promoting student development and institutional change. Although expenditures exceeded the value of LSAHE to communities, value increased each year, suggesting that long-term positive returns may occur.